Cloning and characterization of the Haemophilus influenzae Rd rec-1+ gene. - Stuy, J H (1989)
The Haemophilus influenzae Rd rec-1+ gene was cloned from a partial chromosomal digest into a plasmid vector as a 20-kilobase-pair (kbp) BstEII fragment and then subcloned. The smallest subclone with rec-1+ activity carried a 3.1-kbp EcoRI fragment. The identity of the rec-I gene in these clones was confirmed by transforming an Rd strain carrying a leaky rec-1 mutation (recA4) to resistance to methyl methanesulfonate (MMS) by using whole or digested plasmids. It was demonstrated that the Rec+ phenotype of the MMSr transformants was linked to the strA, novAB, and mmsA loci, as expected if the recA4 allele had been replaced by rec-1+. In growing cultures (rec-1 or rec+), all rec-1+-carrying plasmids induced near-maximal levels of transformability when their hosts reached stationary phase; these levels are 100 to 1,000 times higher than the values seen with strains not carrying a Rec plasmid. Transfer of the 3.1-kbp subclone was greatly reduced compared with transfer of similarly sized vector plasmids, and the resulting transformants grew slowly; this suggests an explanation of my failure to directly clone this fragment from chromosomal DNA digests. Transfer of a rec-1+ plasmid to a very poorly genetically transformable H. influenzae Rb strain resulted in greatly increased transformability. Transfer of such plasmids to a noncompetent H. influenzae Rc strain did not render this strain competent. It is suggested that transformability of Rd and Rb strains is limited by rec-1 expression but that the noncompetence of Rc has some other basis.